Low optical polarization at the core of the optically thin jet of M87. Issue 2 (8th June 2020) - Fresco, A Y; Fernández-Ontiveros, J A; Prieto, M A; Acosta-Pulido, J A; Merloni, A
ABSTRACT: We study the optical linear and circular polarization in the optically thin regime of the core and jet of M87. Observations were acquired two days before the Event Horizon Telescope (EHT) campaign in early 2017 April. A high degree (∼20 per cent) of linear polarization ( P lin ) is detected in the bright jet knots resolved at $\sim 10\, to\, 23\, \rm {arcsec}$ ($0.8{-}1.8\, \rm {kpc}$ ) from the centre, whereas the nucleus and inner jet show P lin ≲ 5 per cent. The position angle of the linear polarization shifts by ∼90° from each knot to the adjacent ones, with the core angle perpendicular to the first knot. The nucleus was in a low level of activity ( P lin ∼ 2–3 per cent), and no emission was detected from HST -1. No circular polarization was detected either in the nucleus or the jet above a 3 σ level of P circ ≤ 1.5 per cent, discarding the conversion of P lin into P circ . A disordered magnetic field configuration or a mix of unresolved knots polarized along axes with different orientations could explain the low P lin . The latter implies a smaller size of the core knots, in line with current interferometric observations. Polarimetry with EHT can probe this scenario in the future. A steep increase of both P lin and P circ with increasing frequency is expected for the optically thin domain, above the turnover point. This work describes the methodology to recover the four Stokes parameters using a λ/4 waveplate polarimeter.